Pengaruh Keselamatan Kesehatan Kerja (K3) dan Disiplin Kerja Terhadap Kinerja Karyawan Pada Fave Hotel Kuta Kartika Plaza - Choirulloh, Muhammad; Irwanti, Ni Ketut Dewi; Ardani, Ni Nyoman (Universitas Triatma Mulya, 2022)
Employee performance is one of the things that need to be considered in a company or organization, because it can affect work discipline and safety. Occupational health in a company. The problem raised in this study is whether occupational health safety (X1) affects employee performance at Fave Hotel Kuta Kartika Plaza, whether work discipline (X2) affects employee performance (Y) at Fave Hotel Kuta Kartika Plaza. whether occupational health safety and work discipline affect employee performance at the Fave Hotel Kuta Kartika Plaza. How big is the influence of occupational health safety and work discipline on employee performance at Fave Hotel Kuta Kartika Plaza and which independent variable has the most dominant influence on employee performance at Fave Hotel Kuta Kartika Plaza. The population in this study amounted to 32 people. The data analysis technique used is descriptive analysis technique, validity test, reliability test, classical assumption test of multiple linear regression analysis, coefficient of determination, F test, and T test. The results of the analysis show the regression model Y = 0.988 + 0.279X1 + 1.081X2. The conclusions obtained are occupational health safety (X1) partially has a positive and significant effect on employee performance (Y) at Fave Hotel Kuta Kartika Plaza which shows b1X1 which is positive. Work discipline (X2) partially has a positive and significant effect on employee performance (Y) at Fave Hotel Kuta Kartika Plaza, this can be seen in the positive b2X2 coefficient. If Occupational Safety and Health (X1) and Work Discipline (X2) are jointly increased by one unit, then Employee Performance will increase by 1.360 (0.279 + 1.081) units. This shows that Occupational Safety and Health (X1), and Work Discipline (X2) have an effect on Employee Performance (Y) at Fave Hotel Kuta Kartika Plaza. The magnitude of the influence of Occupational Safety and Health (X1) and Work Discipline (X2) on Employee Performance (Y) at Fave Hotel Kuta Kartika Plaza is 59.2% while the remaining 40.8% is explained by other variables not examined in this study. The independent variable that has a dominant influence on employee performance can be seen in the Standardized Coefficients Beta value is the occupational health safety variable (X1) which is 0.292 while the work discipline variable (X2) is 0.594.